2006
DOI: 10.1107/s0907444906019895
|View full text |Cite
|
Sign up to set email alerts
|

Structure ofEscherichia colitryptophanase

Abstract: Pyridoxal 5'-phosphate (PLP) dependent tryptophanase has been isolated from Escherichia coli and its crystal structure has been determined. The structure shares the same fold with and has similar quaternary structure to Proteus vulgaris tryptophanase and tyrosine-phenol lyase, but is found in a closed conformation when compared with these two enzymes. The tryptophanase structure, solved in its apo form, does not have covalent PLP bound in the active site, but two sulfate ions. The sulfate ions occupy the phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 51 publications
2
43
0
Order By: Relevance
“…Reproducibly high-binding TNase fragments (defined as peaks at least 10% the height of the base peak) from at least two experiments are shown in Table 1. High-binding TNase fragments specific only to one type of AgNP reinforce the prior observation that In addition, one high-binding protein fragment (NIF-GYQYTIPTHQGR) contains an amino acid (Arg103) that is part of the enzyme's active site (29). Although the amino acid Arg103 is buried within the molecule, the bulk of the peptide containing Arg103 and binding to AgNPs is located on the protein surface.…”
Section: Resultssupporting
confidence: 63%
“…Reproducibly high-binding TNase fragments (defined as peaks at least 10% the height of the base peak) from at least two experiments are shown in Table 1. High-binding TNase fragments specific only to one type of AgNP reinforce the prior observation that In addition, one high-binding protein fragment (NIF-GYQYTIPTHQGR) contains an amino acid (Arg103) that is part of the enzyme's active site (29). Although the amino acid Arg103 is buried within the molecule, the bulk of the peptide containing Arg103 and binding to AgNPs is located on the protein surface.…”
Section: Resultssupporting
confidence: 63%
“…X-ray crystal structural analyses demonstrated that the tryptophanases from E. coli and Pr. vulgaris contain K + -binding sites close to the active site, and that K + ions interact with the O e atom of Glu-72 in one subunit and the backbone carbonyl O atoms of Gly-55 and Pro-275 (Isupov et al, 1998;Ku et al, 2006). P. gingivalis TnaA contained Glu-72 and Gly-55, even though Pro-275 was replaced by Asn.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of E. coli apo enzyme was solved in two crystal forms [26,27] and the structure of a highly homologous Tnase from P. vulgaris was solved in the holo form [28]. The three structures hold significant deviations in the relative orientation of the 'large' and 'small' domains and, as a consequence, show variations in the width of the catalytic site cleft and the geometry of the cofactor binding site.…”
Section: Discussionmentioning
confidence: 99%